2020
DOI: 10.1016/j.jctube.2020.100204
|View full text |Cite|
|
Sign up to set email alerts
|

GeneXpert assay – A cutting-edge tool for rapid tissue diagnosis of tuberculous lymphadenitis

Abstract: Background The most prevalent clinical entity of extra pulmonary tuberculosis is tuberculous lymphadenitis. However, it resembles other granulomatous conditions pathologically and obtaining tissue for microbiological diagnosis is also difficult. Thus it is a challenging task for diagnosis and early initiation of management. Fine needle aspiration cytology and biopsy are the diagnostic methods generally used to obtain the lymph node samples for histopathological and microbiological diagnosis. Mycob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
1
0
1
Order By: Relevance
“…In this study, 3.1% of participants were infected with rifampicin-resistant gene positive M. tuberculosis which is in line with the study conducted in Gondar, Ethiopia 3.9% 24 , India (2.9%) 25 , and Kenya (3.7%) 26 . A study conducted in Hawassa, Ethiopia among patients suspected of pulmonary TB revealed a prevalence of rifampicin resistance of 1.24% which is lower than the current study 27 .…”
Section: Discussionsupporting
confidence: 88%
“…In this study, 3.1% of participants were infected with rifampicin-resistant gene positive M. tuberculosis which is in line with the study conducted in Gondar, Ethiopia 3.9% 24 , India (2.9%) 25 , and Kenya (3.7%) 26 . A study conducted in Hawassa, Ethiopia among patients suspected of pulmonary TB revealed a prevalence of rifampicin resistance of 1.24% which is lower than the current study 27 .…”
Section: Discussionsupporting
confidence: 88%
“…But the overall RIF resistance, or 3% (2/67), is almost similar. 31 A RIF resistance pattern of 7.8% (7/89) among GeneXpert positive cases were shown by another report, which happened to be again lower than the finding from this study. But the overall RIF resistance pattern, 4.8% (7/145), was shown to be slightly higher than the report from this study.…”
Section: Discussioncontrasting
confidence: 78%